Pengembangan Buku â€œAksi Santriâ€ Sebagai Upaya Early Detection Penyakit Kulit - Cahyati, Widya Hary; Siyam, Nur; Hasan, Karnowo (Jurusan Ilmu Kesehatan Masyarakat, Fakultas Ilmu Keolahragaan, Universitas Negeri Semarang, Indonesia, 2021)
Personal hygiene and environmental sanitation greatly affect the incidence of infectious diseases. Skin and respiratory diseases are often occur in boarding schools. Skin disease is the most common disease in developing countries. It was 20-80% of population. The intervention of this study was education about the prevention and control of skin diseases in a boarding house. It was conducted by developing a book entitled â€œAKSI SANTRIâ€ (Ayo Jaga Kulit Sehat Santri Mandiri). The research was conducted in June 2019 until September 2019 at SMPIT Bina Amal Semarang which is a boarding school. The data instrument was a questionnaire to measure students' knowledge, attitudes, and practices in preventing and controling skin diseases. Respondents in this study were students at SMPIT Bina Amal Gunungpati Semarang. Based on the research results, it was concluded that the activity of providing education through counseling by providing the book